Pathogenicity of local isolate virus BHV-1 as the aetiological agent of Infectious Bovine Rhinotracheitis in Bali Cattle - Rini I Damayanti; Sudarisman . (Jurnal Ilmu Ternak dan Veteriner, 2005)
Infectious Bovine Rhinotracheitis is a disease of cattle characterised by clinical signs of the upper respiratory tract, reproductive tract and nervous system. A study to define the pathogenicity of four BHV-1 local isolates has been conducted. Fourteen Bali cattle that were free of BHV-1 has been selected and divided into four treatment groups. Each group of three was infected with virus isolate I, II, III and IV respectively with approximately a dose of 108TCID50 /10 ml and two cattle were used as control animals. Isolate I and III were originated from semen from IBR positive bulls number G 867 and G 148 respectively whereas isolate II was collected from vaginal mucosa and isolate IV was from nasal mucosa of IBR positive cattle treated with dexamethasone. Clinical response, gross-pathological and histopathological changes were observed. Immunohistochemical staining was applied to detect the antigen in tissue section. The results show that the BHV-1 local isolates could produce IBR syndrome namely fever and changes in the respiratory and reproductive tracts even though the clinical responses seemed to be disappeared by 21 days PI. Grossly there were hyperaemic nasal and vaginal mucosa and pneumonia whereas histologically there were non suppurative rhinitis, tracheitis, pneumonia and vulvovaginitis. Immunohistochemically the antigen was detected in the nasal concha and trachea. Dexamethasone treatment at 60-64 days PI could produce less severe clinical features and the second necroppsy at 69 days PI also results in less severe pathological responses. The findings also suggest that the pathogenicity of BHV-1 local isolates were as follows: isolates I, II, IV and III.     Key Words: Pathogenicity, BHV-1, Infectious Bovine Rhinotracheitis (IBR), Bali Cattle